2008
DOI: 10.1111/j.1600-0560.2008.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic pemphigus with negative direct immunofluorescence in epidermis or mucosa but positive findings in adnexal structures

Abstract: Negative DIF findings in epithelia do not rule out the diagnosis of PNP, and the presence of IgG and/or C3 at the intercellular level of adnexal structures can help establish this diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Our findings of positive reactivity in dermal blood vessels, especially in the upper dermis and neurovascular skin appendices are suggestive of possible antigenicity for these structures in ABDs. Finally, recent studies have shown positive reactivity to eccrine and sebaceous glands in ABDs utilizing IIF and DIF [31][32][33][34][35]. In regard to the positive patterns seen in the dermis(possibly associated with cell junctions and/or telocytes), we were able to recently demonstrate activation of both multiple proteases and protease inhibitors following the same patterns of positivity we are describing here [36].…”
Section: Followed the Same Pattern As Fibrinogensupporting
confidence: 81%
“…Our findings of positive reactivity in dermal blood vessels, especially in the upper dermis and neurovascular skin appendices are suggestive of possible antigenicity for these structures in ABDs. Finally, recent studies have shown positive reactivity to eccrine and sebaceous glands in ABDs utilizing IIF and DIF [31][32][33][34][35]. In regard to the positive patterns seen in the dermis(possibly associated with cell junctions and/or telocytes), we were able to recently demonstrate activation of both multiple proteases and protease inhibitors following the same patterns of positivity we are describing here [36].…”
Section: Followed the Same Pattern As Fibrinogensupporting
confidence: 81%
“…Antibodies against envoplakin and periplakin are believed to be the most sensitive and specific indicators of disease 39 . However, the development of plakin autoantibodies has been reported as delayed, limited, or absent in a number of cases of PAMS 40–42 . Both desmoglein (Dsg) 1 and 3 antibodies also have been found in patients with PAMS 43 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…This finding raises the question of whether periadnexal direct immunofluorescence (DIF) findings could offer reasonable, proxy diagnostic information in situations where the epidermis or DEJ cannot be evaluated. Although this hypothesis has not been specifically investigated previously, a prior study reported three patients with paraneoplastic autoimmune multiorgan syndrome (paraneoplastic pemphigus) who were found to have intercellular immunoglobulin (Ig) G and IgM deposits surrounding adnexal structures on DIF testing, when DIF findings of the DEJ were absent …”
mentioning
confidence: 99%